2010
DOI: 10.1075/ijcl.15.2.07uso
|View full text |Cite
|
Sign up to set email alerts
|

Choice of strategies in realizations of epistemic possibility in English and Lithuanian

Abstract: The paper deals with the qualitative and quantitative parameters of equivalence between the realizations of epistemic possibility in English and Lithuanian. The focus of the contrast is on the auxiliary and adverb strategies (van der Auwera et al. 2005) in English (can,could,may,mightvs.maybe,perhaps,possibly) as opposed to the corresponding modal verb and adverb/particle strategies in Lithuanian (galeti“can/could/may/might” vs.gal,galgi,galbut,rasi,lyg ir“maybe/perhaps/possibly”). The purpose of the corpus-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Alongside modal verbs, considerable attention has been devoted to sentence adverbials expressing modal meanings (Usonienė & Šolienė 2010;Šolienė 2012, 2013Šinkūnienė 2012). Studies into realizations of epistemic possibility and necessity have shown that, like in Slavic languages, epistemic meanings in Lithuanian tend to be coded by adverbials or particles rather than by modal verbs, for the latter are not highly grammaticalized elements (Usonienė & Šolienė 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside modal verbs, considerable attention has been devoted to sentence adverbials expressing modal meanings (Usonienė & Šolienė 2010;Šolienė 2012, 2013Šinkūnienė 2012). Studies into realizations of epistemic possibility and necessity have shown that, like in Slavic languages, epistemic meanings in Lithuanian tend to be coded by adverbials or particles rather than by modal verbs, for the latter are not highly grammaticalized elements (Usonienė & Šolienė 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Alongside modal verbs, considerable attention has been devoted to sentence adverbials expressing modal meanings (Usonienė & Šolienė 2010;Šolienė 2012, 2013Šinkūnienė 2012). Studies into realizations of epistemic possibility and necessity have shown that, like in Slavic languages, epistemic meanings in Lithuanian tend to be coded by adverbials or particles rather than by modal verbs, for the latter are not highly grammaticalized elements (Usonienė & Šolienė 2010). As evidenced by the qualitative and quantitative findings obtained from the parallel corpus ParaCorp, English modal verbs of necessity and possibility are rendered into Lithuanian by a variety of adverbials displaying culture-specific conceptualization of epistemic modality (Šolienė 2012, 2013).…”
Section: Introductionmentioning
confidence: 99%